Electrochemical Characteristics and Supercapacitance of the Self-Assembled Catocene Complex on Carbon Microfiber Electrode - sajjad Damiri; Zahra Samiei; Hamid reza Pouretedal (شیمی کاربردی روز)
To prevent a potential energy crisis in the near future, it is necessary to develop high-performance energy storage devices, such as supercapacitors (SCs). In this study, we fabricated a thin film of a new redox catalyst, catocene, on a carbon microfiber electrode (Cat/CMF) using a self-assembled method. We then investigated its electrochemical behaviour in an aqueous sodium sulfate electrolyte. Different techniques were used to evaluate the surface quality of the thin film and its iron content, including scanning electron microscopy (SEM), laser-induced breakdown spectroscopy (LIBS), and attenuated total reflection infrared spectroscopy (ATR). The efficiency and specific capacity of the electrodes were then assessed using cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), and galvanostatic charge-discharge (GCD) methods in a three-electrode system. Electrochemical tests revealed that the redox processes are diffusion-controlled, exhibiting battery-like behaviour. The cathodic transfer coefficient is close to 0.48, and the charge transfer resistance of the modified electrode is improved up to 23 times compared to the bare electrode. At a current density of 0.55 A/g, the specific capacity of the Cat/CMF electrode is 39.76 F/g. At a current density of 0.83 A/g, the catocene thin film exhibits a supercapacitance behaviour with an energy density of 2.5 Wh/kg and a power density of 373.8 W/kg.